Solvothermal preparation and electrochemical characteristics of Sb2Se3@C nanorods in quasi-solid-state batteries. (November 2022) - Xu, Guoli; Ma, Lei; Gu, Chengqian; Jie, Zhihui; Cui, Xuan; Zhang, Chen; Liu, Lei
Abstract: Antinomy(III) selenide (Sb2 Se3 ) nanorods were successfully prepared using a simple solvothermal method and then carbon-coated employing an ex-situ coating process with glucose as the carbon source. The composition and morphology of the prepared samples were characterized by X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy, and transmission electron microscopy. In electrochemical investigations, Sb2 Se3 @C nanorods presented initial specific discharge capacities of 626.0 mAh·g −1 and 319.9 mAh·g −1 at 0.1 C and 1 C in a half-cell structure, respectively, with capacity retentions of 66.4 and 81.8% after 100 cycles. Electrochemical impedance spectroscopy analysis and galvanostatic intermittent titration technique tests revealed that carbon coating effectively promotes both the electronic and ionic conductivities of the Sb2 Se3 @C material, which is beneficial for its electrochemical performance. A Sb2 Se3 @C/Li1.3 Al0.3 Ti1.7 (PO4 )3 /LiFePO4 quasi-solid-state battery was also assembled and delivered a specific discharge capacity of 332.4 mAh·g −1 at 0.2 C with a capacity retention of 60.1% after 100 cycles. In this work, Sb2 Se3 @C nanorods were successfully explored as anode material for quasi-solid-state lithium batteries. Graphical abstract: Image, graphical abstract